2021
DOI: 10.2147/opth.s296510
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Experience with Lifitegrast Ophthalmic Solution (Xiidra®) in the US and Canada: Retrospective Study of Patient Characteristics, Treatment Patterns, and Clinical Effectiveness in 600 Patients with Dry Eye Disease

Abstract: Purpose This study evaluated real-world treatment of dry eye disease (DED) with lifitegrast. Patients and Methods Ophthalmologists and optometrists treating patients with DED were invited to participate through a healthcare provider (HCP)-based panel. HCPs completed a provider survey and contributed data toward a chart review for up to five qualifying patients with DED who initiated lifitegrast ophthalmic solution (index date) between 01/01/2017 (US) or 01/01/2018 (Cana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“… 22 The RWE chart review study was an IRB-approved non-interventional, retrospective, longitudinal cohort study using patient charts from both the US and Canada that were obtained through a healthcare provider panel. 21 The study design and eligibility criteria for each study have been published previously. 21 , 22 Details of the IRBs of the SONATA and RWE studies are provided in Appendix 1 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“… 22 The RWE chart review study was an IRB-approved non-interventional, retrospective, longitudinal cohort study using patient charts from both the US and Canada that were obtained through a healthcare provider panel. 21 The study design and eligibility criteria for each study have been published previously. 21 , 22 Details of the IRBs of the SONATA and RWE studies are provided in Appendix 1 .…”
Section: Methodsmentioning
confidence: 99%
“… 22 The recently published US/Canada real-world evidence (RWE) chart review study demonstrated that the majority of patients receiving lifitegrast treatment had a considerable reduction in overall treatment burden and improvement in DED signs and symptoms 6 months after lifitegrast initiation. 21 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lifitegrast is structurally similar to ICAM-1 and acts as a competitive antagonist to block LFA-1 and ICAM-1 binding and hence reduce the release of inflammatory factors ( 145 ). Lifitegrast (5%) reduces dry eye scores and ocular discomfort with a good safety and tolerability profile ( 146 ). Experimental studies have shown that Lifitegrast can inhibit the levels of IL-1β, IFN-γ and IL-10, and can increase the number and spread of conjunctival goblet cells ( 147 ).…”
Section: Anti-inflammatory Treatment For Dry Eye Diseasementioning
confidence: 99%
“…Experimental studies have shown that Lifitegrast can inhibit the levels of IL-1β, IFN-γ and IL-10, and can increase the number and spread of conjunctival goblet cells ( 147 ). It was approved by the FDA in 2016 to be a novel drug for the treatment of DED ( 146 ).…”
Section: Anti-inflammatory Treatment For Dry Eye Diseasementioning
confidence: 99%